Proceedings of the 8th ACM Conference on Recommender Systems 2014
DOI: 10.1145/2645710.2645726
|View full text |Cite
|
Sign up to set email alerts
|

Cold-start news recommendation with domain-dependent browse graph

Abstract: Online social networks and mash-up services create opportunities to connect different web services otherwise isolated. Specifically in the case of news, users are very much exposed to news articles while performing other activities, such as social networking or web searching. Browsing behavior aimed at the consumption of news, especially in relation to the visits coming from other domains, has been mainly overlooked in previous work. To address that, we build a BrowseGraph out of the collective browsing traces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Popular news portals, such as Google News [15], Yahoo! News [62], The New York Times [61], Washington Post [54] [10], among others have gained increasing attention from a massive amount of online news readers.…”
Section: News Recommender Systemsmentioning
confidence: 99%
“…Popular news portals, such as Google News [15], Yahoo! News [62], The New York Times [61], Washington Post [54] [10], among others have gained increasing attention from a massive amount of online news readers.…”
Section: News Recommender Systemsmentioning
confidence: 99%
“…Indeed, studying the users browsing patterns, Liu et al [20] showed that more recent clicks have a considerably higher value to predict future actions than the historical browsing record. Finally, Trevisiol et al [27] exploited the BrowseGraph in order to build some user models in the news domain, and recommend the next article the user is going to visit. They introduced the concept of ReferrerGraph, which is a BrowseGraph built with sessions that are generated by the same referrer domain.…”
Section: Browsegraphmentioning
confidence: 99%
“…For the purpose of this study, we took a sample of Yahoo News network's 1 user-anonymized log data collected in 2013. The dataset used in this work has been extracted from the data built in [27], that was used with the purpose to study the news consumption with respect to the Referrer URL. In this section we summarize how we built the dataset and the graphs, but the reader may refer to the aforementioned paper for further details.…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations